2015
DOI: 10.1021/acsami.5b08202
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced-Emissive Molecule Incorporated into Polymeric Nanoparticulate as FRET Donor for Observing Doxorubicin Delivery

Abstract: Tetraphenylethene (TPE) derivatives characterized with distinct aggregation-induced-emission, attempted to aggregate with doxorubicin (Dox) to formulate the interior compartment of polymeric nanoparticulate, served as fluorescence resonance energy transfer (FRET) donor to promote emission of acceptor Dox. Accordingly, this FRET formulation allowed identification of Dox in complexed form by detecting FRET. Important insight into the Dox releasing can be subsequently explored by extracting complexed Dox (FRET) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…The attached PGMA was further functionalized with ethanediamine to obtain UiO‐PGEDA with a crowded cationic external shell as polymer brushes onto the established MOF kernel, which are helpful to enhance the stability of the MOF nanoparticles. Furthermore, functional tetraphenylethene (TPE) derivative served as a fluorescence resonance energy transfer (FRET) donor, and (DOX) as an acceptor were strategically utilized and incorporated into the external shell of the aforementioned cationic nanoparticles via electrostatic interactions. The formulated superstructures are postulated to not only afford as a DOX delivery system but also enable in situ observation of DOX release since the liberation of DOX from TPE and UiO‐PGEDA composite could be estimated by monitoring the decrease in the emission of FRET acceptor …”
Section: Methodsmentioning
confidence: 99%
“…The attached PGMA was further functionalized with ethanediamine to obtain UiO‐PGEDA with a crowded cationic external shell as polymer brushes onto the established MOF kernel, which are helpful to enhance the stability of the MOF nanoparticles. Furthermore, functional tetraphenylethene (TPE) derivative served as a fluorescence resonance energy transfer (FRET) donor, and (DOX) as an acceptor were strategically utilized and incorporated into the external shell of the aforementioned cationic nanoparticles via electrostatic interactions. The formulated superstructures are postulated to not only afford as a DOX delivery system but also enable in situ observation of DOX release since the liberation of DOX from TPE and UiO‐PGEDA composite could be estimated by monitoring the decrease in the emission of FRET acceptor …”
Section: Methodsmentioning
confidence: 99%
“…6 Moreover, FRET is a core phenomenon in photosynthesis, 7,8 organic photovoltaics, 9 lighting sources, 10,11 biosensing, [12][13][14] or drug delivery tracing. 15 Furthermore, for practical applications, two requirements are necessary for the FRET process to occur: (1) a substantial overlap of the donor emission spectrum with the acceptor absorption; (2) an appropriate linker and distance between the donor and the acceptor. 16 The light-harvesting system, which collects sunlight efficiently and funnels the excitation energy to the reaction center, which converting solar to chemical energy, plays a very important role in natural photosynthesis.…”
mentioning
confidence: 99%
“…The fluorescence of EPI (green) and FRET-mediated Por (red) were basically overlapping in different time points so that the process of drug release from the nanoparticles in tumor cell was explored. In the first hour, the intensity of red light was strong and that of EPI was almost no light, which showed that the EPI was in the core of nanoparticles to evoke FRET effect [39]. With the time elongated to 2 h, the red FRET signal gradually reduced and the green fluorescence of EPI in the cytoplasm became stronger.…”
Section: Resultsmentioning
confidence: 99%